Gas as a transitional fuel - Stern, J; Stoppard, M; Bergmann, B; Bros, T; Pirani, S (Oxford Institute for Energy Studies, 2008)
Jonathan Stern asks whether the future for international gas trade is constrained; Michael Stoppard looks at LNG growth to 2010; Burckhard Bergmann assesses European gas markets and the interplay of competition, climate protection and supply security; Thierry Bros considers that the UK gas model is a system hard to justify; Simon Pirani explains the pricing policies for Russian gas based on European netbacks.